Analisis Efektivitas Edukasi Perpajakan Bagi Generasi Gen Z Melalui Program Pajak Bertutur Untuk Meningkatkan Kesadaran Pajak Di KPP Pratama Jakarta Tamansari, Jakarta Barat - Kopipah, Kopipah (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research stems from the problem of low levels of tax compliance and awareness in Indonesia, especially among the Effectiveness, Tax Education, Gen Z, Tax Talk. Gen Z generation, which is a significant challenge in increasing tax compliance and awareness. This is due to the lack of socialization of tax education itself. This research aims to analyze the effectiveness of tax education. For the Gen Z Generation through the Tax Talk Program to Increase Tax Awareness at KPP Pratama Jakarta Tamansari, West Jakarta in 2023 as well as identifying the obstacles faced and efforts to overcome these obstacles. This research uses qualitative research with both primary and secondary data collection techniques. The results of the research show that the speech tax program is not yet fully effective. Indicator one shows that the achievement of objectives is quite effective, the integration indicators are effective and the adaptation indicators are not yet fully effective. The obstacles faced are the problem of unpredictable facilities and infrastructure and limited space. Limit the number of participants. Efforts made are to bring in reserve facilities and infrastructure from the KPP which should be able to provide a more adequate place so that it can accommodate many participants..